Marjin Pemasaran Ternak Kerbau Ditingkat Peternak dan Pedagang Berdasarkan Harga Jual: Buffalo Livestock Marketing Value Margin Level and Traders Based on Price - Rusdiana, S; Kusumaningrum, Diana Andrianita (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2018)
The research was conducted in Cibarani Village, Cisata Subdistrict, Paneglang Regency, Banten Province, in 2016. The research used field survey method. To know the value of each marketing margin and its profit value, using questionnaire method of questionnaire data to 10 respondents of buffalo breeders, 5 intermediary traders, 3 large traders and 2 market/meat traders from each data were analyzed economically. The while primary data and secondary data are analyzed by using value of marketing margin analysis. The purpose of this research is to know the marketing margin of buffalo cattle at the level of farmers, small pedanag, traders and market/meat pedangan.Hasil research results at the level of breeders marketing margin I sebear Rp.575.000,- with a share of 5%, profit on the level of cattle traders marketing margin II amounting to Rp.400.000,- with a share of 4.4% and profit at the level of trader III marketing margin of Rp.403.000,- with a share of 4.5% and profit at market/meat market margin level of marketing IV of Rp.305,500,- with a share of 4.3%. From each of the interest margin and the share value shows the buffalo price ratio, which is the difference of each level of livestock traders.